Development of Online Learning based on the Art-Based Lateral Thinking Model to Promote Creative Thinking for Undergraduate Students - Khotpratum, Phongthep; Simmatun, Prawit; Teemauangsai, Sanit (Rajapark Journal, 2024)
The objectives of this research were to 1) examine the current and expected needs of undergraduate students regarding online learning and 2) develop online learning based on the art-based lateral thinking model to promote creative thinking (OALT model). This study employed a mixed-methods research design across three distinct phases. The papers presented in Phases 1 and 2 investigate the need for assessment and model development for creative thinking development. The target groups encompassed nine instructors, nine subject matter experts, and a sample group, obtained through cluster sampling, consisting of 400 undergraduate students. Data was collected through document analysis, an in-depth interview, and a questionnaire. The subsequent data analysis was quantitative and qualitative statistics, including frequency distribution, percentage, mean, standard deviation, the PNImodified index, and content analysis. The research results were found as follows: 1) The current and expected needs that promote creativity, with the PNImodified values ranging between 0.25 and 0.85, showed that the aspect with the highest PNImodified was the process of promoting creative thinking. And 2) the OALT model consisted of 7 components: 1) Masterwork Analysis; 2) Conceptual Exploration; 3) Lateral Thinking Exercises; 4) Artistic Expression; 5) Reflection and Integration; 6) Collaborative Projects; and 7) Feedback and Revision. The assessment results indicated that the appropriateness of the model was at the highest level.